A Cu-Co / ZrO2 interface-regulated bimetallic catalyst, its preparation method and application
Patent Information
- Application Number
- CN202611213936.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的在于解决现有技术中糠醛加氢制备戊二醇过程中催化剂活性中心调控能力不足、目标产物选择性较低以及副产物生成较多的技术问题,提供一种Cu-Co/ZrO2界面调控型双金属催化剂及其制备方法和应用
1)本发明以ZrO2为载体,Cu和Co双金属为活性组分,采用浸渍、干燥、煅烧及还原处理的方法制备了Cu-Co/ZrO2双金属催化剂。本发明的制备方法能够使Cu、Co活性组分均匀分散于ZrO2载体表面,并增强Cu-Co活性组分之间的协同作用,其中Cu物种促进糠醛羰基加氢,Co物种促进氢活化及C-O键活化,二者之间产生电子协同作用,提高了催化剂对糠醛加氢反应路径的调控能力。同时,ZrO2载体具有较强的金属-载体相互作用,能够稳定Cu-Co活性中心,抑制金属颗粒团聚,提高催化剂的稳定性,而且本发明所提供的制备方法工艺简单,操作条件温和,具有良好的应用前景。
Smart Images

Figure CN122999199A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of biomass catalytic conversion and heterogeneous catalysis, and particularly to a Cu-Co / ZrO2 interface-regulated bimetallic catalyst, its preparation method, and its application. Background Technology
[0002] With the continuous depletion of fossil resources and the increasing severity of environmental problems, the development and utilization of renewable biomass resources to produce high-value-added chemicals has become a current research hotspot. Furfural is an important biomass-based platform compound that can be obtained from hemicellulose and lignocellulose resources through hydrolysis and dehydration. Its molecular structure contains active functional groups such as furan rings and aldehyde groups, which can be converted into various high-value-added chemicals through hydrogenation, ring-opening, and rearrangement reactions. Among them, pentylene glycol compounds, as important fine chemical intermediates, have wide applications in polyester materials, plasticizers, coatings, pharmaceuticals, and fragrances. Therefore, achieving highly selective conversion of furfural to pentylene glycol has significant economic value and application prospects.
[0003] Currently, the hydrogenation of furfural to pentanediol mainly relies on supported metal catalysts. Traditional Cu-based catalysts, due to the strong carbonyl hydrogenation ability of Cu species, can promote the conversion of furfural to furfuryl alcohol and further ring-opening hydrogenation. However, the single Cu active center has limited ability to regulate CO bond breaking, molecular rearrangement, and subsequent hydrogenation processes, leading to the easy formation of various byproducts and making it difficult to achieve high selectivity for target products such as 1,2-pentanediol, 1,4-pentanediol, and 1,5-pentanediol. Furthermore, Cu particles are prone to agglomeration during the reaction, reducing active sites and thus decreasing catalyst stability and cycle performance. Traditional SiO2 supports have high specific surface area and good dispersibility, but their strong surface inertness and weak interaction with metals mean that the selectivity of catalysts in complex reaction systems still needs improvement.
[0004] Therefore, developing a highly active and selective catalyst to achieve highly selective conversion of furfural to 1,2-pentanediol and 1,5-pentanediol is of great significance for promoting the high-value utilization of biomass. Summary of the Invention
[0005] The purpose of this invention is to solve the technical problems of insufficient catalyst active center control, low target product selectivity, and excessive by-product generation in the process of furfural hydrogenation to pentanediol. This invention provides a Cu-Co / ZrO2 interface-controlled bimetallic catalyst, its preparation method, and its application.
[0006] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing a Cu-Co / ZrO2 interface-regulated bimetallic catalyst, comprising the following steps: (1) The ZrO2 support was impregnated in a Cu-Co mixed impregnation solution to obtain the catalyst precursor; (2) The catalyst precursor is calcined and reduced in sequence to obtain the Cu-Co / ZrO2 interface-regulated bimetallic catalyst.
[0007] Preferably, the Cu-Co mixed impregnation solution in step (1) contains a copper precursor, a cobalt precursor and a solvent; The copper precursor is one or more of copper nitrate, copper acetate, and copper chloride; The cobalt precursor is one or more of cobalt nitrate, cobalt acetate, and cobalt chloride; The solvent is one or more of water, ethanol, and 1,4-dioxane.
[0008] Preferably, the mass ratio of copper active component, cobalt active component and ZrO2 support in Cu-Co / ZrO2 interface-regulated bimetallic catalyst is 0.5~2:1:10~30. The concentration of metal ions in the Cu-Co mixed impregnation solution is 50~250 mmol / L.
[0009] Preferably, the immersion treatment in step (1) is carried out at a temperature of 20~60℃ for 2~4h.
[0010] Preferably, the calcination temperature in step (2) is 300~600℃ and the heating rate is 1~10℃ / min.
[0011] Preferably, the calcination time in step (2) is 2 to 6 hours.
[0012] Preferably, the atmosphere for the reduction treatment in step (2) is hydrogen, and the heating rate is 1~10℃ / min.
[0013] Preferably, the reduction treatment in step (2) is carried out at a temperature of 200~500℃ for 1~5h.
[0014] The present invention also provides a method for preparing the Cu-Co / ZrO2 interface-regulated bimetallic catalyst.
[0015] This invention also provides the application of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst in the selective hydrogenation of furfural to prepare pentanediol.
[0016] This invention provides a method for preparing a Cu-Co / ZrO2 interface-controlled bimetallic catalyst, comprising the following steps: placing a ZrO2 support in a Cu-Co mixed impregnation solution for impregnation treatment to obtain a catalyst precursor; sequentially subjecting the catalyst precursor to calcination and reduction treatments to obtain the Cu-Co / ZrO2 interface-controlled bimetallic catalyst.
[0017] The beneficial effects of this invention are: 1) This invention uses ZrO2 as a support and Cu and Co bimetallic components as active components to prepare a Cu-Co / ZrO2 bimetallic catalyst through impregnation, drying, calcination, and reduction treatment. The preparation method of this invention enables the Cu and Co active components to be uniformly dispersed on the surface of the ZrO2 support and enhances the synergistic effect between the Cu and Co active components. Specifically, Cu species promote the carbonyl hydrogenation of furfural, while Co species promote hydrogen activation and CO bond activation, resulting in an electronic synergistic effect that improves the catalyst's ability to regulate the furfural hydrogenation reaction pathway. Simultaneously, the ZrO2 support exhibits strong metal-support interactions, which can stabilize the Cu-Co active centers, inhibit metal particle agglomeration, and improve catalyst stability. Furthermore, the preparation method provided by this invention is simple, operates under mild conditions, and has good application prospects.
[0018] 2) The Cu-Co / ZrO2 bimetallic catalyst of this invention can be used for the selective hydrogenation of furfural to prepare pentanediol compounds. Compared with the Cu-Co / SiO2 catalyst, the catalyst of this invention can improve the selectivity for the formation of 1,2-pentanediol and 1,5-pentanediol, with the yield of 1,2-pentanediol reaching 31.81% and the yield of 1,5-pentanediol reaching 10.91%, while reducing the formation of 1,4-pentanediol byproduct, thus improving the selectivity of the target product in the furfural hydrogenation reaction. Attached Figure Description
[0019] Figure 1 This is a transmission electron microscope (TEM) image of the bimetallic catalyst in Example 1; Figure 2 This is a transmission electron microscope (TEM) image of the bimetallic catalyst in Comparative Example 1 at 100 nm. Figure 3 This is a transmission electron microscope (TEM) image of the bimetallic catalyst in Comparative Example 1 at 50 nm. Figure 4 The image shows the HAADF-STEM image of the bimetallic catalyst in Example 1. Figure 5 This is a diagram showing the elemental distribution of Co in the bimetallic catalyst of Example 1; Figure 6 This is a Cu elemental distribution diagram of the bimetallic catalyst in Example 1; Figure 7 This is a diagram showing the O element distribution of the bimetallic catalyst in Example 1; Figure 8 The Zr elemental distribution diagram is shown for the bimetallic catalyst in Example 1. Figure 9 The image shows the HAADF-STEM image of the bimetallic catalyst in Comparative Example 1. Figure 10 The elemental distribution of Cu in the bimetallic catalyst of Comparative Example 1 is shown. Figure 11 The elemental distribution of Co in the bimetallic catalyst of Comparative Example 1 is shown in the diagram. Figure 12 This is a diagram showing the O element distribution of the bimetallic catalyst in Comparative Example 1. Figure 13 The image shows the elemental distribution of Si in the bimetallic catalyst of Comparative Example 1. Figure 14 The XRD patterns of the bimetallic catalysts in Example 1 and Comparative Example 1 are shown. Figure 15 The XRD patterns before and after the reaction with the bimetallic catalyst in Comparative Example 1 are shown. Figure 16 The images show the XRD patterns of the bimetallic catalyst before and after the reaction in Example 1. Figure 17 The N2 adsorption-desorption isotherms are shown for the bimetallic catalysts of Example 1 and Comparative Example 1. Figure 18 The pore size distribution diagrams are for the bimetallic catalysts of Example 1 and Comparative Example 1. Figure 19 Comparison of Cu elemental LMM Auger electron spectra of bimetallic catalysts in Example 1 and Comparative Example 1; Figure 20 Comparison of X-ray photoelectron spectra of Co element in Example 1 and Comparative Example 1 bimetallic catalysts; Figure 21 Comparison of the X-ray photoelectron spectra of O element for the bimetallic catalysts of Example 1 and Comparative Example 1; Figure 22 This is a comparison graph of H2- temperature-programmed desorption of the bimetallic catalysts in Example 1 and Comparative Example 1; Figure 23 This is a comparison graph of CO2 temperature-programmed desorption of the bimetallic catalysts in Example 1 and Comparative Example 1; Figure 24 The graph shows the performance and cycle stability evaluation of the bimetallic catalysts used in Example 1 and Comparative Example 1 for the hydrogenation of furfural. Detailed Implementation
[0020] This invention provides a method for preparing a Cu-Co / ZrO2 interface-regulated bimetallic catalyst, comprising the following steps: (1) The ZrO2 support was impregnated in a Cu-Co mixed impregnation solution to obtain the catalyst precursor; (2) The catalyst precursor is calcined and reduced in sequence to obtain the Cu-Co / ZrO2 interface-regulated bimetallic catalyst.
[0021] In this invention, the Cu-Co mixed impregnation solution in step (1) contains a copper precursor, a cobalt precursor and a solvent.
[0022] In this invention, the copper precursor is one or more of copper nitrate, copper acetate, and copper chloride.
[0023] In this invention, the cobalt precursor is one or more of cobalt nitrate, cobalt acetate, and cobalt chloride.
[0024] In this invention, the solvent is one or more of water, ethanol, and 1,4-dioxane.
[0025] In this invention, a copper precursor, a cobalt precursor, and a solvent are mixed under stirring conditions. The mixing temperature is preferably 10-40°C, more preferably 15-35°C, and even more preferably 20-30°C. The mixing time is preferably 10-120 min, more preferably 20-100 min, and even more preferably 40-80 min. After stirring, a Cu-Co mixed impregnation solution is obtained.
[0026] In this invention, the mass ratio of copper active component, cobalt active component and ZrO2 support in the Cu-Co / ZrO2 interface-regulated bimetallic catalyst is preferably 0.5~2:1:10~30, more preferably 0.9~1.3:1:16~22, and even more preferably 1.0~1.2:1:18~20.
[0027] In this invention, the concentration of metal ions in the Cu-Co mixed impregnation solution is preferably 50-250 mmol / L, more preferably 100-200 mmol / L, and even more preferably 140-160 mmol / L.
[0028] In this invention, the temperature of the immersion treatment in step (1) is preferably 20~60℃, more preferably 30~50℃, and even more preferably 35~45℃; the time is preferably 2~4h, more preferably 2.5~3.5h, and even more preferably 2.8~3.2h; the immersion treatment is carried out under stirring conditions.
[0029] In this invention, after the impregnation treatment is completed, drying is carried out. The drying temperature is preferably 80~120℃, more preferably 90~110℃, and even more preferably 95~105℃; the drying time is preferably 6~24h, more preferably 10~20h, and even more preferably 14~16h.
[0030] In this invention, the calcination temperature in step (2) is preferably 300~600℃, more preferably 350~550℃, and even more preferably 400~500℃; the heating rate is preferably 1~10℃ / min, more preferably 2~8℃ / min, and even more preferably 4~6℃ / min.
[0031] In this invention, the calcination time in step (2) is preferably 2 to 6 hours, more preferably 3 to 5 hours, and even more preferably 3.5 to 4 hours; the calcination is carried out in an air atmosphere.
[0032] In this invention, the atmosphere for the reduction treatment in step (2) is hydrogen, and the heating rate is preferably 1~10℃ / min, more preferably 2~8℃ / min, and even more preferably 4~6℃ / min.
[0033] In this invention, the temperature of the reduction treatment in step (2) is preferably 200~500℃, more preferably 250~450℃, and even more preferably 300~400℃; the time is preferably 1~5h, more preferably 2~4h, and even more preferably 2.5~3h.
[0034] In this invention, due to the electronic interactions between the Cu-Co bimetals and the strong metal-support interactions of the ZrO2 support, Cu and Co species form different degrees of reduced states during the reduction process. Therefore, the catalyst surface exhibits Cu... 0 / Cu + / Cu 2+ and Co 0 / Co 2+ Coexisting multivalent structure.
[0035] The present invention also provides a method for preparing the Cu-Co / ZrO2 interface-regulated bimetallic catalyst.
[0036] In this invention, Cu and Co active components are loaded on the ZrO2 support surface of the catalyst. The Cu active component is Cu oxide and / or metallic Cu species; the Co active component is Co oxide and / or metallic Co species. The active components are regulated by the ZrO2 support to form Cu-Co active centers with synergistic catalytic effects.
[0037] This invention also provides the application of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst in the selective hydrogenation of furfural to prepare pentanediol.
[0038] In this invention, the selective hydrogenation of furfural to prepare pentanediol is mainly based on the principle of heterogeneous catalytic hydrogenation reaction. The conversion of furfural into high-value-added pentanediol compounds is achieved through processes such as hydrogen activation, carbonyl hydrogenation, CO bond activation, and molecular rearrangement. During the reaction, hydrogen first dissociates at the metal active site to form active hydrogen species. Subsequently, the active hydrogen reacts with the aldehyde group in the furfural molecule to generate intermediate products, which further form 1,2-pentanediol, 1,4-pentanediol, and 1,5-pentanediol through furan ring opening, CO bond breaking, and hydrogenation reactions. Therefore, the structure of the catalyst's active site and its ability to regulate the reaction pathway are key to achieving highly selective conversion of furfural.
[0039] In this invention, Cu possesses strong carbonyl hydrogenation ability, which can promote the selective hydrogenation of furfural aldehyde groups; Co has good hydrogen activation ability and CO bond activation ability, which can promote furan ring cleavage and subsequent hydrogenation processes. After Cu and Co form a bimetallic active center, electronic effects and synergistic effects occur between them, which can regulate the adsorption behavior of reaction intermediates and promote the formation of the target pentanediol product. At the same time, the ZrO2 support has strong thermal stability and adjustable surface acid-base properties, which can enhance the metal-support interaction, improve the dispersibility of Cu and Co active components, and stabilize the dispersion state of Cu-Co active components, thereby improving the catalytic activity and selectivity of the catalyst.
[0040] In this invention, the specific steps for selective hydrogenation of furfural to prepare pentanediol using the above-mentioned Cu-Co / ZrO2 bimetallic catalyst include: adding a certain amount of Cu-Co / ZrO2 bimetallic catalyst to a high-pressure reactor, adding a mixture of furfural and isopropanol as the reaction system, sealing the reactor, purging the air with hydrogen, and then charging with 2 MPa of hydrogen as the reaction pressure; subsequently, carrying out the hydrogenation reaction under a set temperature condition, cooling the reactor after the reaction, separating the reaction liquid by filtration, and analyzing the liquid phase products by gas chromatography to obtain products such as 1,2-pentanediol, 1,4-pentanediol, and 1,5-pentanediol.
[0041] The technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0042] Example 1
[0043] Weigh 0.197 g of copper nitrate trihydrate and 0.237 g of cobalt nitrate hexahydrate and add them to 9 mL of deionized water. Stir at 30 °C for 120 min until completely dissolved to obtain a Cu-Co mixed impregnation solution.
[0044] Subsequently, 0.9 g of ZrO2 support was added, and the mixture was stirred and aged at 25°C for 2 h to allow Cu and Co species to be fully adsorbed onto the surface of the ZrO2 support.
[0045] The obtained solid was dried in an oven at 110℃ for 12 h to obtain the Cu-Co / ZrO2 catalyst precursor.
[0046] The catalyst precursor was then placed in a muffle furnace and heated to 500℃ at a rate of 3℃ / min, and calcined in air for 3 hours to obtain a CuO-CoOx / ZrO2 catalyst. The mass ratio of copper active component, cobalt active component and ZrO2 support in the catalyst was 0.0518:0.0480:0.900.
[0047] Finally, the calcined catalyst was placed in a reduction furnace and reduced to 300℃ at 5℃ / min under H2 atmosphere for 3 h to obtain a Cu-Co / ZrO2 interface-controlled bimetallic catalyst.
[0048] Comparative Example 1
[0049] The difference between Comparative Example 1 and Example 1 is that the support was replaced with a SiO2 support, while the rest was the same as in Example 1, resulting in a Cu-Co / SiO2 bimetallic catalyst.
[0050] The Cu-Co bimetallic catalysts prepared in Example 1 and Comparative Example 1 were used for the hydrogenation reaction of furfural. The specific method included: adding 0.075 g of Cu-Co bimetallic catalyst, 35 ml of isopropanol, and 0.4 g of furfural to a high-pressure reactor. Before the reaction, hydrogen gas was introduced into the reactor to replace the air, and 2 MPa H2 was introduced as the reaction pressure. The furfural hydrogenation reaction was then carried out at a set temperature. After the reaction, the catalyst was separated by filtration, and the liquid product was analyzed by gas chromatography.
[0051] To investigate the cyclic stability of the catalyst, a recycling test was conducted on the catalyst after the reaction. The specific steps are as follows: After the reaction, the catalyst was separated by filtration, washed with isopropanol, and then dried in an oven to obtain the recycled catalyst. The dried catalyst was directly used in the next furfural hydrogenation reaction, with the reaction conditions consistent with the first reaction. The above operations were repeated for multiple cycles, and the liquid phase products after each cycle were analyzed by gas chromatography to examine the changes in catalytic activity and product selectivity of the Cu-Co bimetallic catalyst during continuous use.
[0052] Transmission electron microscopy image of the bimetallic catalyst in Example 1 is shown below. Figure 1 As shown, the transmission electron microscope (TEM) image of the bimetallic catalyst in Comparative Example 1 at 100 nm is as follows. Figure 2As shown, the transmission electron microscope image at 50 nm is as follows: Figure 3 As shown. From Figure 1 As can be seen from the figure, the active components are uniformly dispersed on the surface of the ZrO2 support, and no obvious large particle aggregation was observed. Figure 2 and Figure 3 It can be seen that the active components in the Cu-Co / SiO2 catalyst mainly exist in the form of nanoparticles with relatively large particle sizes.
[0053] Example 1: HAADF-STEM image of the bimetallic catalyst is shown below. Figure 4 As shown, the Co elemental distribution of the bimetallic catalyst in Example 1 is as follows: Figure 5 As shown, the distribution of Cu elements is as follows: Figure 6 As shown, the distribution of O elements is as follows: Figure 7 As shown, the Zr element distribution is as follows Figure 8 As shown. From Figures 4-8 It can be seen that Cu, Co, O, and Zr elements are evenly distributed.
[0054] The HAADF-STEM image of the bimetallic catalyst in Comparative Example 1 is shown below. Figure 9 As shown, the distribution of Cu elements is as follows: Figure 10 As shown, the distribution of Co element is as follows: Figure 11 As shown, the distribution of O elements is as follows: Figure 12 As shown, the Si element distribution is as follows: Figure 13 As shown. From Figures 9-13 It can be seen that the elements Cu, Co, O, and Si are distributed relatively evenly.
[0055] The XRD patterns of the bimetallic catalysts in Example 1 and Comparative Example 1 are shown below. Figure 14 As shown, the XRD patterns of the bimetallic catalyst in Comparative Example 1 before and after the reaction are as follows: Figure 15 As shown, the XRD patterns of the bimetallic catalyst before and after the reaction in Example 1 are as follows. Figure 16 As shown. From Figures 14-16 It can be seen that both the Cu-Co / SiO2 and Cu-Co / ZrO2 catalysts exhibit diffraction peaks related to Cu and Co species. Cu mainly exists in metallic form, while Co species show a coexistence of metallic and oxidized states. Simultaneously, a diffraction signal related to the Cu-Co alloy was observed around 44°, indicating a strong interaction between Cu and Co species. After the furfural hydrogenation reaction, the Cu characteristic peaks in the Cu-Co / SiO2 catalyst significantly weakened, and strong Co oxide-related diffraction peaks appeared, indicating oxidation and structural changes of the active component during the reaction. The Cu-Co / ZrO2 catalyst, however, maintained the Cu and Co related diffraction characteristics after the reaction, indicating that the ZrO2 support can enhance the metal-support interaction and improve the structural stability of the Cu-Co active component.
[0056] The N2 adsorption-desorption isotherms of the bimetallic catalysts in Example 1 and Comparative Example 1 are shown below. Figure 17 As shown, the aperture distribution diagram is as follows: Figure 18 As shown. From Figure 17 and Figure 18 It can be seen that both Cu-Co / SiO2 and Cu-Co / ZrO2 catalysts exhibit significant nitrogen adsorption behavior, with the adsorption amount increasing rapidly in the high relative pressure region, indicating that both catalysts possess a mesoporous structure. The pore size distribution curves show that the pore sizes of both catalysts are mainly distributed within the mesoporous range. While the pore structure of the catalysts undergoes some changes after the reaction, the overall mesoporous structure is still maintained, indicating that the Cu-Co bimetallic catalyst has good structural stability.
[0057] The Cu elemental LMM Auger electron spectra of the bimetallic catalysts in Example 1 and Comparative Example 1 are shown below. Figure 19 As shown, the X-ray photoelectron spectroscopy of Co element is as follows: Figure 20 As shown, the X-ray photoelectron spectrum of element O is compared to... Figure 21 As shown. From Figures 19-21 As can be seen from the XPS test results, Cu exists on the surface of both Cu-Co / ZrO2 and Cu-Co / SiO2 catalysts. 0 / Cu + / Cu 2+ and Co 0 / Co 2+ It contains various active species in different valence states. Compared with Cu-Co / SiO2 catalyst, the electronic states of Cu and Co species in Cu-Co / ZrO2 catalyst change significantly, and the O 1s peak shifts, indicating that the ZrO2 support can enhance the metal-support interaction and regulate the electronic structure of Cu-Co bimetallic active centers, thereby facilitating the adsorption activation and selective hydrogenation of furfural molecules.
[0058] H2-Programmed Desorption of Bimetallic Catalysts in Example 1 and Comparative Example 1 Figure 22 As shown, CO2- temperature-programmed desorption is compared to, for example... Figure 23 As shown. From Figure 22 It can be seen that both Cu-Co / SiO2 and Cu-Co / ZrO2 catalysts exhibit hydrogen desorption peaks at both low and high temperatures, indicating the presence of hydrogen adsorption sites of varying intensities on the catalyst surface. Specifically, the high-temperature hydrogen desorption peak of the Cu-Co / ZrO2 catalyst decreases from 422℃ to 326℃, suggesting that the ZrO2 support can modulate the adsorption strength of hydrogen species by the Cu-Co active centers, enhancing the migration ability of hydrogen species and thus facilitating the hydrogenation reaction. Figure 23It can be seen that both Cu-Co / SiO2 and Cu-Co / ZrO2 catalysts have basic sites of varying strengths. The Cu-Co / SiO2 catalyst exhibits CO2 desorption peaks at 99℃, 361℃, 472℃, and 590℃, while the Cu-Co / ZrO2 catalyst mainly shows desorption peaks at 84℃ and 341℃. This indicates that the ZrO2 support alters the distribution of basic sites on the catalyst surface, thus regulating the adsorption behavior of reactants and intermediates on the catalyst surface.
[0059] The performance and cycle stability of the bimetallic catalysts used in Example 1 and Comparative Example 1 for the hydrogenation of furfural are evaluated as follows: Figure 24 As shown, Figure 24 In the figure, a shows the effect of Cu-Co / ZrO2 catalyst on the distribution of furfural hydrogenation products at different reaction temperatures; b shows the effect of Cu-Co / ZrO2 catalyst on the distribution of furfural hydrogenation products at different reaction times; c compares the furfural hydrogenation product distribution of Cu-Co / SiO2 and Cu-Co / ZrO2 catalysts; d shows the selectivity of Cu-Co / SiO2 and Cu-Co / ZrO2 catalysts for pentanediol products; e shows the cycle stability of Cu-Co / SiO2 catalyst; and f shows the cycle stability of Cu-Co / ZrO2 catalyst. From a and b, it can be seen that the distribution of furfural hydrogenation products can be controlled by adjusting the reaction temperature and reaction time. When the reaction temperature is 220℃ and the reaction time is 3 h, the catalyst exhibits superior catalytic performance. From c and d, it can be seen that compared with Cu-Co / SiO2 catalyst, Cu-Co / ZrO2 catalyst can significantly change the product distribution, improve the selectivity of 1,2-pentanediol and 1,5-pentanediol, and reduce the formation of 1,4-pentanediol. As can be seen from e and f, both catalysts exhibit a certain degree of cycling stability, with the Cu-Co / ZrO2 catalyst maintaining good catalytic performance even after multiple cycles. This further demonstrates that the introduction of the ZrO2 support can improve the selectivity of the target pentanediol product and enhance the catalyst's stability.
[0060] As can be seen from the above embodiments, the present invention provides a Cu-Co / ZrO2 bimetallic catalyst, its preparation method, and its application. The present invention prepares the Cu-Co / ZrO2 catalyst using impregnation, drying, calcination, and reduction methods. The ZrO2 support enhances the synergistic effect between the Cu and Co bimetals, thereby controlling the furfural hydrogenation reaction pathway and improving the selectivity of 1,2-pentanediol and 1,5-pentanediol.
[0061] Compared with Cu-Co / SiO2 catalysts, the catalyst of this invention can improve the formation capacity of the target pentanediol product and has good cycle stability.
[0062] In this invention, the preparation of pentanediol by hydrogenation of furfural using the Cu-Co / ZrO2 bimetallic catalyst mainly includes hydrogen activation, carbonyl hydrogenation, CO bond activation, and subsequent hydrogenation reaction.
[0063] During the reaction, Cu species can promote the selective hydrogenation of furfural carbonyl, while Co species have strong hydrogen activation and CO bond activation capabilities. The synergistic effect between Cu and Co can regulate the electronic structure of the active center and improve the hydrogen activation and reaction intermediate conversion capabilities.
[0064] Meanwhile, the ZrO2 support has strong metal-support interaction and adjustable surface acid-base properties, which can promote the uniform dispersion of Cu and Co species and stabilize the bimetallic active centers. It can also promote the directional activation of CO bonds by regulating the adsorption behavior of furfural and its intermediates, thereby changing the reaction pathway and improving the selectivity of 1,2-pentanediol and 1,5-pentanediol.
[0065] Compared with traditional SiO2 supports, ZrO2 has stronger metal-support interactions and surface acid-base regulation capabilities, which can further change the electronic environment of the Cu-Co bimetallic interface, allowing furfural molecules to adsorb onto the catalyst surface in a manner more conducive to the formation of the target product, thereby promoting the formation of 1,2-pentanediol and reducing the formation of the non-target product 1,4-pentanediol.
[0066] Therefore, by constructing a Cu-Co / ZrO2 interface synergistic structure, this invention achieves the synergistic effect between the metal hydrogenation site and the support regulation site, thereby promoting the highly selective conversion of furfural to the target pentanediol product.
[0067] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a Cu-Co / ZrO2 interface-regulated bimetallic catalyst, characterized in that, Includes the following steps: (1) The ZrO2 support was impregnated in a Cu-Co mixed impregnation solution to obtain the catalyst precursor; (2) The catalyst precursor is calcined and reduced in sequence to obtain the Cu-Co / ZrO2 interface-regulated bimetallic catalyst.
2. The preparation method of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst as described in claim 1, characterized in that, In step (1), the Cu-Co mixed impregnation solution contains a copper precursor, a cobalt precursor, and a solvent; The copper precursor is one or more of copper nitrate, copper acetate, and copper chloride; The cobalt precursor is one or more of cobalt nitrate, cobalt acetate, and cobalt chloride; The solvent is one or more of water, ethanol, and 1,4-dioxane.
3. The preparation method of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst as described in claim 2, characterized in that, The mass ratio of copper active component, cobalt active component and ZrO2 support in Cu-Co / ZrO2 interface-regulated bimetallic catalyst is 0.5~2:1:10~30. The concentration of metal ions in the Cu-Co mixed impregnation solution is 50~250 mmol / L.
4. The preparation method of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst as described in claim 3, characterized in that, The immersion treatment in step (1) is carried out at a temperature of 20~60℃ for 2~4h.
5. The preparation method of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst as described in claim 4, characterized in that, In step (2), the calcination temperature is 300~600℃ and the heating rate is 1~10℃ / min.
6. The preparation method of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst as described in claim 5, characterized in that, The calcination time in step (2) is 2~6 hours.
7. The preparation method of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst as described in claim 6, characterized in that, In step (2), the atmosphere for the reduction treatment is hydrogen, and the heating rate is 1~10℃ / min.
8. The preparation method of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst as described in claim 7, characterized in that, In step (2), the reduction treatment temperature is 200~500℃ and the time is 1~5h.
9. The Cu-Co / ZrO2 interface-controlled bimetallic catalyst prepared by the method described in any one of claims 1 to 8.
10. The application of the Cu-Co / ZrO2 interface-regulated bimetallic catalyst of claim 9 in the selective hydrogenation of furfural to prepare pentanediol.
